Ultrasound Guided Stellate Ganglion Block with Dexmedetomidine as an Adjuvant in Complex Regional Pain Syndrome (CRPS) - Shrestha, B. R.; Lama, S.; Shrestha, U. (Kathmandu University Medical Journal, 2021)
This is a case report of successful use of ultrasound for stellate ganglion (SG) blocks in CRPS I in 11 patients using local anesthetic bupivacaine with injection dexmedetomidine as an adjunct. Ultrasound helped us to deposit Local anesthetics in target area without any noticeable side effects and trauma to adjacent structures.